Implementasi Peraturan Walikota Samarinda Nomor 02 Tahun 2019 Tentang Sistem Dan Prosedur Pelaksanaan Pemungutan Pajak Daerah Terkait Pajak Sarang Burung Walet Di Kota Samarinda - Yatini; Luvita, Reina (Yuriska: Jurnal Ilmiah Hukum, 2020)
This study aims to determine the implementation of Mayor Regulation Number 02 of 2019 concerning the system and procedures for implementing local tax collection related to swallow’s nest tax in Samarinda City. This research is an Empirical legal research sourced from primary and secondary data. The results showed that the tax collection carried out by the City Revenue Agency in its implementation and implementation was constrained by several factors. So it is advisable to implement a local government tax collection of bird’s nest as well since the issuance of the regulations after the mayor and the local government or the province should consider to help Regional Revenue Agency Samarinda carry out tasks that have been mentioned in the regulations of the mayor.